Day 2 - 1340 - Moritz Heil.pdf - Gill, Philip (Cranfield University, 2023)
Decomposition of NC under different conditions Dr.-Ing. Moritz Heil - Fraunhofer ICT 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'